Impact of Religious Tourism landmarks - Suha Hassan Al Dahwi; Yousif Issa Alwan (Iraqi Journal of Architecture and Planning, 2018)
The most important characteristic of urban cities is the presence of identity characterizes types of architecture. Most of these cities suffer from the decline and deterioration, and become blocks of adjacent buildings, which are copies of a particular architecture and tradition and simulate them. That led to disappear originality. The importance of this research on the link between the role of tourism attraction within the central cities for rooting there urban identity. Through the review of previous studies on the subject of tourist attraction,and after clarify landmarks kind, the research problem has identified as the "Missing of comprehensive knowledge about the role of religious tourist landmarks in dimensions of authenticity urban identity for the city" .The goal of research is reaching to the role of religious tourist landmarks in urban development projects to clarify urban identity authenticity dimensions. The research adopted descriptive analytical method and draw the most important variables, indicators and vocabulary, which has been employed in the application of the study, which included analysis many of elected local development projects.Keywords: Authenticity, Landmark, Religious Tourism landmarks